PENGARUH FASILITAS BELAJAR, MINAT BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 12 PEKANBARU - Marena Olyvia Marena Olyvia; Gimin '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to determine the effect of learning facilities , interest in learning on learning outcomes of economic subjects class XI SMA 12 Pekanbaru . Learning outcomes are influenced by several learning factors such as facilities and interest in learning . Class XI students of SMAN 12 Pekanbaru has a population of 114 students . Based on the results of 54 samples taken randomly in mind that as many as 20 students ( 30 % ) having a very complete home study with a value of 74. The highest percentage of students who have interest in learning at home are very high as many as 17 students ( 30 % ) with The highest percentage of 51 . The primary data obtained through kuosioner about learning facilities at home and interest in learning at home while secondary data obtained from the study hasl documentation in SMA 12 Pekanbaru . The data has been collected by the authors then analyzed by regression analysis . Before the authors conducted a regression analysis , data normality test requirements . By using the One - Sample Kolmogorov - Smirnov Test - normal distribution of data known with indigo significance of learning facilities at home 0998 and 0.968 for the significant value of the interest in learning at home . There is a significant relationship between learning facilities at home and interest in learning at home together on learning outcomes . with a count of 12 809 f greater than t table at 3:18 . While partially on learning facility there is no significant influence on learning outcomes as t , t table ( 0529 < 2.00758 ) with a percentage of 0.9 % , but interest in learning affects the learning outcomes for t > t table ( 2,800 > 2.00758 ) with perentase of 25.2 % .. As for the influence of learning facilities and interest in learning on learning outcomes can be seen from the value of the R Square sebsar 33.4 % , while the remaining 66.6 % is influenced by other factors not examined in this study .Keywords : learning facilities , interest in learning , learning outcomes